A Pedagogy of Reconciliation: Transformative education in a Canadian context - Jeremy Siemens (Canadian Society for Studies in Education, 2017)
Of the 94 Calls to Action within the Truth and Reconciliation Commission of Canada's (TRC) Final Report, almost one-fifth focused on matters of education. This represents a strong belief that formal teaching and learning can positively impact the relationship between Indigenous and non-Indigenous people in Canada. However, there is no established framework for such education. Reflecting on the report and drawing on critical pedagogy scholarship, I work towards a better understanding of the necessary pedagogy required for education for reconciliation. Recognizing the ways in which the work of "reconciliation" is situated in particular cultural, historical, and social realities, I outline an approach to education for reconciliation that is attentive to the Canadian context. Drawing on both critical pedagogy and Indigenous knowledges, this framework attempts to honour the TRC Final Report, offering an approach that is both pointedly critical and deeply relational.